Activin A and Heart Function in Severe Preeclampsia: Insights From Global Longitudinal Strain - Sriyanti, Roza; Permatasari, Ressy; Kino, Kino (Journal of Health and Nutrition Research, 2025)
Preeclampsia, a serious pregnancy complication affecting 2–5% of women globally, is a leading cause of maternal and fetal mortality. Its prevalence in Indonesia ranges from 0.8–7% depending on parity. Associated with long-term cardiovascular risks, recent research suggests that elevated maternal activin A levels may play a causal role in linking severe preeclampsia to subsequent cardiovascular complications, particularly through mechanisms involving cellular damage, including to the heart. The aim of this study was to assess the correlation between Activin A circulating level and cardiac ventricular function as assessed by cardiac global longitudinal strain (GLS) in severe preeclampsia. A cross-sectional study was conducted at M. Djamil Hospital, Padang, West Sumatera, Indonesia with a total of 31 patients with severe preeclampsia. The Enzyme-Linked Immunosorbent Assay (ELISA) as used to determine the level of Activin A in the blood serum. Ventricular function was assessed from the global longitudinal strain using echocardiographic evaluation. The mean level of Activin A was 2.97 ± 1.91 ng/mL. From the echocardiographic evaluation, the mean cardiac GLS value was 18.01 ± 3.27%.  The correlation between activin A levels and cardiac ventricular function was analyzed using Pearson's correlation test, which showed a strong negative correlation (r = -0.718, p < 0.001). This indicates that higher activin A levels are significantly associated with lower GLS values, demonstrating worse ventricular function.